Analisis Implementasi Scoring Bank Indonesia (BI) Checking dalam Keputusan Analisis Pembiayaan pada Bank Syariah - Nurhidayah, Alimah; Lestari Nasution, Annio Indah; Kusmilawaty, Kusmilawaty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aimed to analyze the implementation of the SLIK OJK system in financing decision-making at Bank Sumut KCP Syariah Kisaran and to evaluate the challenges and opportunities arising from its application. Using a qualitative case study approach, data was collected through in-depth interviews and document analysis. The findings revealed that while the SLIK OJK system helped reduce the Non-Performing Financing (NPF) ratio from 4.1% to 2.8%, it was unable to accommodate prospective clients from the informal sector who had high business potential but were not recorded in formal financial databases. The centralized and algorithm-driven nature of the system demonstrated a bias against social justice and did not permit branch units to exercise discretion in assessing applicants' character, socio-economic conditions, and moral track records. Within the framework of maqasid sharia, this situation created a dissonance between prudential banking principles and the imperative of public welfare. As a solution, this study proposed a hybrid Scoring approach, integrating systematic quantitative analysis with qualitative evaluations by branch units, to establish an inclusive and adaptive Islamic financing mechanism. The findings contributed significantly to the reformulation of risk assessment policies and the enhancement of financing governance rooted in sharia-based values.